2009
DOI: 10.1016/j.jinsphys.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Two novel defensin-encoding genes of the Chagas disease vector Triatoma brasiliensis (Reduviidae, Triatominae): Gene expression and peptide-structure modeling

Abstract: Defensins are cysteine-rich peptides involved in the innate immunity of insects and many other organisms. In the present study, two novel defensin-encoding cDNAs and the respective genomic DNAs (def3 and def4) of Triatoma brasiliensis were identified and their tissue-specific and temporal expression was characterized. Both of the deduced mature peptides consisted of 43 amino acid residues and were highly similar to previously identified triatomine defensins (81.4-100%). Semi-quantitative RT-PCR data showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 60 publications
0
28
0
2
Order By: Relevance
“…A previous study – based on structural properties – showed a high similarity between R. prolixus DefA and DefB while DefC differed significantly, forming two distinct groups after a phylogenetic analysis [60]. These authors suggested that the various defensins have different functions.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study – based on structural properties – showed a high similarity between R. prolixus DefA and DefB while DefC differed significantly, forming two distinct groups after a phylogenetic analysis [60]. These authors suggested that the various defensins have different functions.…”
Section: Discussionmentioning
confidence: 97%
“…4), which contributes to enhanced parasite infectivity. We hypothesize that the interaction of cyclophilin 19 with other protein ligands, such as proline-containing defensin-like peptides (5,62,63) or ␣-globin (1, 29, 51), may also contribute to aspects of in vivo parasite differentiation.…”
Section: And 2)mentioning
confidence: 99%
“…Other factors that affect trypanosome development are the AMPs of the insect vector and only defensins have been found in triatomines, such as R. prolixus and T. brasiliensis (Lopez et al 2003, Araújo et al 2006, Waniek et al 2009). Defensins mainly lyse Gram + bacteria, but they can also kill Gram -bacteria, fungi and parasites (Boulanger et al 2006).…”
Section: Nosmentioning
confidence: 99%
“…Defensins mainly lyse Gram + bacteria, but they can also kill Gram -bacteria, fungi and parasites (Boulanger et al 2006). In triatomines, different isoforms of defensins have been observed (Lopez et al 2003, Araújo et al 2006, Waniek et al 2009). In R. prolixus, defensin genes are expressed after bacterial inoculations and the activation of immune responses increases the gene transcription in the fat body and the gut (Lopez et al 2003).…”
Section: Nosmentioning
confidence: 99%